Investigation on the mobility and stability in organic thin film transistors consisting of bilayer gate dielectrics. Issue 1 (1st October 2015) - Sun, Qi‐Jun; Zhuang, Jiaqing; Yan, Yan; Zhou, Ye; Han, Su‐Ting; Zhou, Li; Roy, Vellaisamy A. L.
Abstract : One of the important problems in organic thin film transistors (OTFTs) is the existence of traps on oxide gate dielectrics which degrades the device performance and stability. By modifying the dielectric oxide surface, we obtained devices with bilayer dielectrics that show high mobility and good operational stability compared with the devices based on bare silicon dioxide dielectric layer. The average carrier mobility increases from 0.19 (without surface modification) to 0.35, 0.51, and 0.97 cm 2  V −1  s −1 after employing a thin layer of hexamethyldisilazane (HMDS), polymethylmethacrylate (PMMA), and polystyrene (PS), respectively. The PS‐modified device exhibits the superior mobility, operational, and air stability in comparison with other devices. We ascribe these results to fewer traps caused by the OH group or OH‐induced water at the interface of semiconductor and the dielectric layer. In our study, the morphology of the semiconductor layer seems to have limited influence on the mobility and operational stability.